(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3YR Hf aVGFd Hf YKeGf GdaQVi GdMehi , heMeO Hf eMeO GdUeQLi s)
(3ChdgG (B:s
(3HGH GdQGA , aUd GdCda bhdg (B: (3CHQ (B: (3GdEHQI hGMOI GdEHQ , hEHQI GdPQGY eSJObgG , hCHQJ GdcdH CWYeJg GdEHQI ai GdNHQ hai GdMOjK GdeDef cGcdH GdeCHhQ s
(3BNQgG (B:s
(3hSeYJ CHG GdZhK jbhd gh GdHYhQ HGdHGA JLYdg eCNhPkG ef GdHYQ hGdHhd hGdjYGQI HGdaJM Cf jMed Ydi GdfGbI GdaMd eYGQVI jbGO EdjgG Ef GTJgG hEdG adGe Je HGH GdQGA ef cJGH GdUMGM ai GddZI jJdhg HGH GdRGi , aUd GdCda , CHR GdXHi s
(3HgG fXGe WeSs
(3JMGhQ YdjgG fGSNGfs
(3eged GdfbW CMjGfkGs
(3hbO bhHd gPG GdLRA ai BNQ TgQ ThGd SfI (B659(3g` Ydi fSNI jGbhJ GdcGJH GdPi fbd fSNJg ef fSNI HNW CHj egd eMeO Hf Ydi GdgQhi GdPi fbd fSNJg ef NW GdeDda s
(3fSNI YGTQI s
(3HgG fXGe GdJYbjHIs
Keywords: (3GddZIs